Some Strength Tests' Percentile Degree As Indicators for Selecting Iraqi Youth Weightlifters Aged 14 – 16 Years old - Jassim, Mouyed; Kamil, Omar (Journal of Physical Education, 2018)
Some Strength Tests' Percentile Degree As Indicators for Selecting Iraqi Youth Weightlifters Aged 14 – 16 Years oldThe importance of the research lies in providing percentile degree as indicators for selecting weightlifters using some special abilities in youth weightlifters aged (14 – 16) years old. The problem was the lack of percentile for selecting youth weightlifters. The researcher used the experimental method and the subjects were (65) weightlifters aged 14 – 16 years old. The data was collected treated using proper statistical operations. The researchers concluded a set of percentile degree for selecting weightlifters. Finally they recommended evaluating performance of some tests and generalizing them.